Implications of recruiting foreign nurses in local healthcare sector - Noor Hasliza, Che Seman * (MalaysiaKini, 2023)
The global landscape is currently facing a pronounced nursing deficit, with estimates suggesting a shortage of nearly 13 million nurses by 2030, as reported by the International Council of Nurses.